EFEKTIFITAS KOMBINASI GREEN TEA EXTRACT DAN SENOBI BREATHING EXERCISE UNTUK MENURUNKAN PREVALENSI LEMAK TUBUH REMAJA PADA KONDISI AKUT - Nafi'ah Nafi'ah; Mu’jizatillah Mu’jizatillah; Jhudi Bonosari Soediono (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2020)
In last decade there has been an increase prevalence of overweight adolescents. Various strategies and products have been evaluated in effort to prevent and treat overweight using Green Tea Extract (GTE) and Senobi Breathing Exercise (SBE). However, the effect of GTE and SBE on decreasing adolescent body fat percentage in acute conditions when combined are unknown. The method used quasi experimental with control group design. The research conducted in Gymnasium laboratory of the Politeknik Unggulan Kalimantan in March 2020. The samples used were aged 18-21 years with BMI 25-29.9. Determination of samples using Federer's formula: (t-1) (n-1) ?15 obtained 4 treatment groups with a sample size of each group are 10 people that divided into: (a) overweight GTE; (b) overweight SBE; (c) overweight GTE and SBE; (d) overweight control . Measurement percentage of body fat in acute conditions shortly after treatment utilize Body Fat Monitor Scale GEA Medical EF 981. Statistical Test using Krusskall Wallis , the results obtained were P> 0.05, which indicates that there was no significant effect of GTE and SBE to reduce prevalence of adolescent body fat in acute conditions. Further research is needed to find out the correct protocol.